Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation